PREACHING AT THE KINGDOM OF GUATEMALA: A TOOL FOR SOCIAL AND POLITICAL HISTORY - Belaubre, Christophe (2016)
This essay rescues the importance of preaching as a practice during the colonial period in Central America. Tridentine priests made an effort for bishops and parish priests to preach the Holy Gospel of Jesus Christ; therefore, they created a body of laws to help in this effort. The Catholic reform should win over Protestantism using these new values that appeared in Europe during the 17th century and consoldated during the 18th century. By analyzing 30 sermons I propose some ideas about the form and diffusion of sermons within the Central American colonial society—I also made a sociologinal presentation of the preaches. I distinguish three kind of sermons: those of the mass which help to instruct parishioners; what I call the extraordinary sermons; and political sermons which multiply after the Napolionic invasión to Spain in 1808.